2016
DOI: 10.1021/acs.nanolett.6b03300
|View full text |Cite
|
Sign up to set email alerts
|

Strong Rashba-Edelstein Effect-Induced Spin–Orbit Torques in Monolayer Transition Metal Dichalcogenide/Ferromagnet Bilayers

Abstract: The electronic and optoelectronic properties of two-dimensional materials have been extensively explored in graphene and layered transition metal dichalcogenides (TMDs). Spintronics in these two-dimensional materials could provide novel opportunities for future electronics, for example, efficient generation of spin current, which should enable the efficient manipulation of magnetic elements. So far, the quantitative determination of charge current-induced spin current and spin-orbit torques (SOTs) on the magne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
219
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 282 publications
(234 citation statements)
references
References 40 publications
11
219
2
2
Order By: Relevance
“…and (3) of the extrinsic SOC of Bychkov‐Rashba type introduced by a transverse electric field . Besides those discussed earlier, proximity effect was also successfully demonstrated in graphene/YIG, graphene/Au, and WSe 2 /CoFeB bilayers . However, the effects of these ‘extrinsic’ SOC are moderate.…”
Section: Beyond Atomic 2d Semiconductorsmentioning
confidence: 57%
See 2 more Smart Citations
“…and (3) of the extrinsic SOC of Bychkov‐Rashba type introduced by a transverse electric field . Besides those discussed earlier, proximity effect was also successfully demonstrated in graphene/YIG, graphene/Au, and WSe 2 /CoFeB bilayers . However, the effects of these ‘extrinsic’ SOC are moderate.…”
Section: Beyond Atomic 2d Semiconductorsmentioning
confidence: 57%
“…A large number of first‐principles calculations have been carried out to study SOC in various materials and they have shown that SOC can split degenerate energy bands, thus modifying the electronic band structures of the materials. Some of the 2D materials such as TMDs show large SOC . However, much work in the field of spin‐orbitronics have been done on bulk materials of heavy elements, such as Ta, W, Ir, Pt, Au, and Bi, due to their large SOC.…”
Section: Beyond Atomic 2d Semiconductorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing experimental studies have exclusively focused on chemical vapor deposition‐grown or mechanically exfoliated TMDs, necessitating additional steps, such as vacuum breaking and physical transfer (onto a substrate), prior to ferromagnet (FM) deposition . These approaches cannot provide the cleanest interface at the atomic level, which is, however, a key factor for achieving large spin signals in relevant devices, such as 2D‐based MTJs as already discussed above.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…[152][153][154][155][156] Existing experimental studies have exclusively focused on chemical vapor deposition-grown or mechanically exfoliated TMDs, necessitating additional steps, such as vacuum breaking and physical transfer (onto a substrate), prior to ferromagnet (FM) deposition. 148,157 These approaches cannot provide the cleanest interface at the atomic level, which is, however, a key factor for achieving large spin signals in relevant devices, 158,159 such as 2D-based MTJs as already discussed above. An MBE-based growth strategy in response to the above issue has been demonstrated, enabling wafer-scale TMDs with full coverage on substrate and contaminationfree FM/TMD interface.…”
Section: Interface-induced Magnetic Phenomenamentioning
confidence: 99%